Light absorption by polar and non-polar aerosol compounds from laboratory biomass combustion - Sengupta, Deep; Samburova, Vera; Bhattarai, Chiranjivi; Kirillova, Elena; Mazzoleni, Lynn; Iaukea-Lum, Michealene; Watts, Adam; Moosmüller, Hans; Khlystov, Andrey (Atmospheric chemistry and physics, 2018)
Fresh and atmospherically aged biomass-burning (BB) aerosol mass is mostly comprised of strongly light-absorbing black carbon (BC) and of organic carbon (OC) with its light-absorbing fraction – brown carbon (BrC). There is a lack of data on the physical and chemical properties of atmospheric BB aerosols, leading to high uncertainties in estimates of the BB impact on air quality and climate, especially for BrC. The polarity of chemical compounds influences their fate in the atmosphere including wet/dry deposition and chemical and physical processing. So far, most of the attention has been given to the water-soluble (polar) fraction of BrC, while the non-polar BrC fraction has been largely ignored. In the present study, the light absorption properties of polar and non-polar fractions of fresh and aged BB emissions were examined to estimate the contribution of different-polarity organic compounds to the light absorption properties of BB aerosols. In our experiments, four globally and regionally important fuels were burned under flaming and smoldering conditions in the Desert Research Institute (DRI) combustion chamber. To mimic atmospheric oxidation processes (5–7 days), BB emissions were aged using an oxidation flow reactor (OFR). Fresh and OFR-aged BB aerosols were collected on filters and extracted with water and hexane to study absorption properties of polar and non-polar organic species. Results of spectrophotometric measurements (absorption weighted by the solar spectrum and normalized to mass of fuel consumed) over the 190 to 900 nm wavelength range showed that the non-polar (hexane-soluble) fraction is 2–3 times more absorbing than the polar (water-soluble) fraction. However, for emissions from fuels that undergo flaming combustion, an increased absorbance was observed for the water extracts of oxidized/aged emissions while the absorption of the hexane extracts was lower for the aged emissions for the same type of fuels. Absorption Ångström exponent (AAE) values, computed based on absorbance values from spectrophotometer measurements, were changed with aging and the nature of this change was fuel dependent. The light absorption by humic-like substances (HULIS) was found to be higher in fuels characteristic of the southwestern USA. The absorption of the HULIS fraction was lower for OFR-aged BB emissions. Comparison of the light absorption properties of different-polarity extracts (water, hexane, HULIS) provides insight into the chemical nature of BB BrC and its transformation during oxidation processes.